Women in TVET: Contestation of Agency and Patriarchal Power for Liberation - Rai, Indra Mani; Joshi, Pashupati (Journal of Education and Research, 2020)
Against the effort made through Technical and Vocational Education and Training (TVET) in ensuring gender equality through providing women with the self/employment opportunities, there exists under-representation of them particularly in male-dominated training courses and jobs. In this context, the paper, based on a qualitative case study of three women who engaged in the courses and then occupations, portrays their struggles for coping with the gender stereotypes of devaluing women’s capability in the context of patriarchal power domination. Visualising from the feminist power perspectives, we came to the insights that the women’s agency (willingness, commitment, motivation, and knowledgeability) contests with the power held by males and patriarchal social structures. The negotiation of within self-power of women and external power of males and society support to unleash them for making a choice of career path.